2015
DOI: 10.4137/cin.s17300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Smoothing Functions in Generalized Additive Models for Spatial Variation in Disease

Abstract: Generalized additive models (GAMs) with bivariate smoothing functions have been applied to estimate spatial variation in risk for many types of cancers. Only a handful of studies have evaluated the performance of smoothing functions applied in GAMs with regard to different geographical areas of elevated risk and different risk levels. This study evaluates the ability of different smoothing functions to detect overall spatial variation of risk and elevated risk in diverse geographical areas at various risk leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Regions with greater population distributions would smooth data from a smaller geographic area than regions with sparse populations. Previous simulation studies evaluated the type I error rate and power of several GAM hypothesis testing methods and showed that GAMs performed well for analyzing spatial patterns of various shape and sizes including non-circular clusters (4348).…”
Section: Methodsmentioning
confidence: 99%
“…Regions with greater population distributions would smooth data from a smaller geographic area than regions with sparse populations. Previous simulation studies evaluated the type I error rate and power of several GAM hypothesis testing methods and showed that GAMs performed well for analyzing spatial patterns of various shape and sizes including non-circular clusters (4348).…”
Section: Methodsmentioning
confidence: 99%
“…LOESS regressions were conducted with the stats package in R [ 58 ]. It employs quadratic polynomial models on a moving collection of data points (termed a neighborhood ) in a TS [ 59 ]. The size of the neighborhood is user defined and referred to as the span of the LOESS model, with greater spans creating more smooth trends because of using a wider collection of surrounding data points, whereas shorter spans resulting in closer fitting to the data.…”
Section: Methodsmentioning
confidence: 99%
“…[30][31][32] We used GAMs because of their flexibility, computational efficiency, power, and sensitivity to detect areas of elevated disease risks. 30,[33][34][35] In each risk situation we used the residential locations at the time of study enrollment, s i , to model the log-odds of disease as log…”
Section: Model Specificationmentioning
confidence: 99%
“…Forms of smoothers that have been used previously in spatial analyses include the locally weighted scatterplot smoothing (LOESS), 36 and the thin plate regression spline (TPRS). 35,37,38 For this study f (s i ) in Equation (2) is the estimate of the spatial log-odds at location s i using TPRS. A thin plate spline (TPS) is a type of regression that estimates a smooth function of multiple predictor variables and the response variable.…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation